Fibromyalgia: do I tackle you with complementary medicines? - Julien Nizard; Françoise Laroche; Fabrice Berna (PAIN Reports, 2025)
Abstract. Recent guidelines for managing fibromyalgia highlight the importance of a graded-care approach, tailoring treatment to predominant symptoms, and appropriately integrating nonpharmacological treatments and complementary medicine (CM). Many fibromyalgia patients turn to nonpharmacological treatment and CM for various reasons, including concerns about medication side effects and persistent symptoms despite pharmacological treatment. In addition, these approaches are sometimes mistakenly, but often, perceived as natural and, therefore, widely accepted as well-tolerated with minimal risks. However, as with many patients using CM, fibromyalgia patients frequently engage in these practices without informing their physicians, often because of fear of a negative reaction. This can occur in contexts that lack adequate safeguards, such as treatment by noncertified practitioners, undocumented practices, excessive costs, or unsafe environments. In this narrative review, we first provide updated definitions of these practices, discuss their potential benefits and associated risks, and explore the challenges in their evaluation. We then summarize key findings from the literature before proposing a structured approach for discussing these practices with fibromyalgia patients. This includes assessing their prior experiences, expectations, and motivations for long-term adherence. We also offer guidance on selecting qualified practitioners and ensuring a sufficiently safe treatment environment. Finally, we highlight essential “red flags” that pain specialists and health care providers should discuss with patients, emphasizing the need for caution or even discontinuation of certain practices when these warning signs are present.